Pembangkitan Ekonomis pada Unit Pembangkit Listrik Tenaga Diesel Telaga Gorontalo Menggunakan Algoritma Genetika - Sabhan Kanata (Universitas Syiah Kuala, 2017)
The increasing daily need towards electrical energy demands for generation companies to conduct operational cost-saving strategy including the generation fuel. One of the strategies that can be done is through economical generation optimization. The genetics algorithm of the heuristics method is known for its ability to overcome the problems characterized as non-linear, non convex, integer/ discrete, not continuous, and a system with a lot of variables. The evaluation technique employing the evolution theory has been applied to the case of IEEE 26 buses power system and diesel power generation in a unit in Telaga, Gorontalo. The result shows that the proposed method is believed to be able to minimize the generation cost better than the previous method. The method is tested by applying for its real system in Telaga, Gorontalo and it is found that the total cost at Rp 20.201.000,00 per hour with total load at 5.000 kW.